2017
DOI: 10.1088/1367-2630/aa56eb
|View full text |Cite
|
Sign up to set email alerts
|

Sputtering and redeposition of ion irradiated Au nanoparticle arrays: direct comparison of simulations to experiments

Abstract: Ion beam processing of surfaces is well known to lead to sputtering, which conventionally is associated only with erosion of atoms from the material. We show here, by combination of experiments and a newly developed Monte Carlo algorithm, that in the case of nanoparticles in a regular twodimensional array on surfaces, the redeposition of sputtered atoms may play a significant role on the system development. The simulations are directly compared to in situ experiments obtained using a dual focused Ga + ion beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The issue is of increased current interest due to the use of increasingly low energies in industrial ion irradiation [17] and also the interest in examining ion modification of single nanostructures where the energies are small to maximize the irradiation effects on the nanostructure [18][19][20]. Some of these studies have shown a large variability in the radiation response of seemingly identical nanorods or nanoparticles [18,19,21], an effect difficult to explain by other means than channeling.…”
Section: Introductionmentioning
confidence: 99%
“…The issue is of increased current interest due to the use of increasingly low energies in industrial ion irradiation [17] and also the interest in examining ion modification of single nanostructures where the energies are small to maximize the irradiation effects on the nanostructure [18][19][20]. Some of these studies have shown a large variability in the radiation response of seemingly identical nanorods or nanoparticles [18,19,21], an effect difficult to explain by other means than channeling.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of the band gap may be due to the increase oh the structural disorder or defects generated due to the ion implantation that formed silver nano-clusters confirmed earlier using (SEM, TEM). Furthermore, the defects are created because of several factors, but the most important are radiation damage and very high local heating through latent tracks [26][27][28][29][30]. As a final result, the optical gap decreases slightly due to the increase of disorder and silver cluster defects in the polymer matrix.…”
Section: Ellipsometric Spectroscopy Analysismentioning
confidence: 99%
“…Probably, isolated electrically charged nanoclusters, when present in the polymer structure, give rise to an electric field within the bulk polymer. The internal fields thus produced strongly affect the band structure [27][28][29][30][31][32][33]. The increase of disorder and radiation damage defects in the structural polymer bonding with increasing silver ion fluences in HDPE results in decrease of optical band gap.…”
Section: Ellipsometric Spectroscopy Analysismentioning
confidence: 99%
“…Besides conventional use of the ion's kinetic energy for tailoring material properties, an increased charge state of the ion also leads to substantial energy deposition [6][7][8][9]. Especially for low-dimensional materials, like nanowires [1], nanodots [10], and two-dimensional (2D) layers [11][12][13], ion irradiation represents a promising tool for defect engineering, which should ideally be confined to the topmost surface layer. For these classes of materials, the presence of defects can strongly affect their electronic [14], optical [15], and mechanical [16] properties.…”
Section: Introductionmentioning
confidence: 99%